Grunty zasobu własności rolnej skarbu państwa w rękach cudzoziemców i podmiotów z udziałem kapitału zagranicznego - Klusek, Tomasz (Land Out of State Treasury Owned Or Rented by Foreigners and Entities with Foreign Capital, 2006)
While managing the property belonging to the State Treasury the Agricultural Property Agency (APA) is entitled to sell or rent agricultural land also to foreigners or entities with foreign capital. The papers is focused on the scope of this phenomenon according to its' development by the end of June 2005.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 426-432